Lithospheric deformation revealed by teleseismic phases SKS PKS and SKKS splitting in the NE margin of the Tibetan plateau - Xia, Xinyu; Gao, Yuan; Wu, Yue (Frontiers in Earth Science, 2024)
The NE margin of the Tibetan plateau influenced by multiple blocks, the regional dynamic model and lithospheric deformation characteristics are still controversial. In this study, 15 years data from permanent broadband seismic stations of the seismic network in the study area were adopted for splitting analyses of teleseismic phases XKS (SKS PKS and SKKS, shortly named XKS) using a grid search method, longer observations provided each station with a large number of clear seismic phases. The results show that the fast wave directions of XKS splitting are oriented toward WNW or NW, with reference to the direction of absolute plate motion, the lithospheric deformation is dominantly driven by the asthenosphere, although there are local variations. On both sides of the Haiyuan fault zone, there is a noticeable variation in lithospheric azimuthal anisotropy, further enhances the possibility that it is an extended boundary of the Tibetan plateau. Rheological anisotropic features on the western side of the Ordos block emphasize the obstruction of the rigid Ordos lithosphere. The crust and mantle seem to be coupled below the Qinling orogen, possibly related to the lateral movement of lithospheric material. However, in the Hexi corridor, there may be layered anisotropy within the lithosphere, which is inferred to relate to the subductions of the Alxa block and the Qilian orogen. The thicker lithosphere on the southern margin of the Alxa block may influence the asthenospheric flow. In addition, anisotropy results at the southeastern edge of the Alxa block and the Yinchuan graben reflect the possibility that the lithosphere may be characterized by a combination of horizontal and vertical movements. These results have greatly improved our understanding of the dynamic models and lithospheric deformation characteristics of the northeastern margin of the Tibetan plateau and adjacent areas.